PENGEMBANGAN MEDIA PEMBELAJARAN TRAINER PENGENDALI ELEKTROMAGNETIK PADA INSTALASI MOTOR LISTRIK DI JURUSAN TEKNIK LISTRIK SMK NEGERI 3 SINGARAJA - gede wijayoga nata renjaya; I Gede Ratnaya; I Putu Suka Arsa (Jurnal Pendidikan Teknik Elektro Undiksha, 2021)
This study aims to make an Electromagnetic Control Trainer in an Electric Motor Installation in the Electrical Engineering Department of SMK Negeri 3 Singaraja to find out the feasibility of the Electrical Motor Installation (IML) subject. This research uses the developmental research method. The list collection in this study was conducted by distributing questionnaires or questionnaires rated by the content or material experts, and media experts. The research results were obtained: the results of the validation test from media experts got a percentage of 93.33% including very feasible quaqualificationsns, and the results of the validation test for content experts or material experts got a percentage of 96, 2% including very feasible qualifications. Based on the results of the research, the learning media for the Electromagnetic Control Trainer in the Electrical Motor Installation in the Electrical Engineering Department of SMK Negeri 3 Singaraja is suitable for use in the learning process of Electrical Motor Installation (IML).